2014
DOI: 10.1111/iej.12411
|View full text |Cite
|
Sign up to set email alerts
|

Effects of JNK1/2 on the inflammation cytokine TNF‐α‐enhanced production of MMP‐3 in human dental pulp fibroblast‐like cells

Abstract: Goda S, Kato Y, Domae E, Hayashi H, Tani-Ishii N, Iida J, Ikeo T. Effects of JNK1/2 on the inflammation cytokine TNF-a-enhanced production of MMP-3 in human dental pulp fibroblast-like cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 25 publications
(40 reference statements)
0
17
0
Order By: Relevance
“…39 The recent study demonstrated enhancement of MMP-3 production in dental pulp fibroblast-like cells when stimulated with TNF-a, suggesting its role in angiogenesis. 40 Level of MMP-3 was also found significantly increase in oral squamous cell carcinoma patients compared to the healthy control. Moreover, the increase expression of MMP-3 correlated with the stage of tumour suggesting the participation of this enzyme in the pathogenesis and progression of the disease.…”
Section: Discussionmentioning
confidence: 70%
“…39 The recent study demonstrated enhancement of MMP-3 production in dental pulp fibroblast-like cells when stimulated with TNF-a, suggesting its role in angiogenesis. 40 Level of MMP-3 was also found significantly increase in oral squamous cell carcinoma patients compared to the healthy control. Moreover, the increase expression of MMP-3 correlated with the stage of tumour suggesting the participation of this enzyme in the pathogenesis and progression of the disease.…”
Section: Discussionmentioning
confidence: 70%
“…Bacterial lipopolysaccharide (LPS)-induced release of pro-inflammatory mediators elevate levels of MMP-1, -2 and -3 in acute pulpitis [109,110]. Release of MMP-3 can activate other MMP members, mediate collagen degradation in the extracellular matrix, induce inflammation and promote angiogenesis [111]. MMP-13 is the major collagenase in dental pulp tissues and is effective in cleaving type II collagen.…”
Section: Anti-mmp Activitiesmentioning
confidence: 99%
“…reported (Goda et al 2015. The protein products of the JNK pathway are involved in apoptosis, neurodegeneration, cell differentiation and proliferation, inflammation and cytokine production mediated by the activation of transcription factors (Goda et al 2015).…”
Section: Molecular Events Involved In Inflammatory Responsesmentioning
confidence: 99%